Robust Ekeland variational principles. Application to the formation and stability of partnerships. (2nd January 2023) - Fakhar, M.; Khodakhah, M. R.; Soubeyran, A.; Zafarani, J.
Abstract : This paper has two parts. The mathematical part provides generalized versions of the robust Ekeland variational principle in terms of set-valued EVP with variable preferences, uncertain parameters and changing weights given to vectorial perturbation functions. The behavioural part that motivates our findings models the formation and stability of a partnership in a changing, uncertain and complex environment in the context of the variational rationality approach of stop, continue and go human dynamics. Our generalizations allow us to consider two very important psychological effects relative to ego depletion and goal gradient hypothesis.